The Education of Students in Hospital Schools: A View from Philosophy, Economics, and Technology - Castro-Ibáñez, Carolina (2023)
Introduction. Hospital schools are an educational environment characterized by the high heterogeneity of their students, encompassing different ages, illnesses, and previous educational repertoires. Pedagogical practices within these schools manifest through dialectical and negotiation processes, occurring in relative times and spaces. Purpose. This study aims to analyze certain tensions that occur in the educational process of students attending hospital schools. Three key factors of the process are part of this analysis. Discussion. Philosophical, economic, and technological aspects intertwine, shaping the current educational landscape within hospital schools. From a philosophical perspective, time and space in hospital schools are presented as dimensions that facilitate the introduction of non-conventional educational approaches, challenging the traditional one. On the economic side, the problematic issue of financing these schools arises due to their particular implementation. Finally, technology emerges as a crucial factor in ensuring the continuity of the educational process for children and young people affected by illness. Conclusion. The three examined factors illustrate how the modifications developed in the context of hospital schools could provide valuable guidance to the mainstream education system. The outbreak of the Covid-19 pandemic has highlighted the imperative need for adaptable and effective mechanisms capable of sustaining the continuity of educational processes for all students. We are invited to learn from out-of-the-ordinary approaches to enrich and strengthen our education system as a whole.